Comparative evaluation on phenolic profiles, antioxidant properties and α-glucosidase inhibitory effects of different milling fractions of foxtail millet. (May 2021) - Zhang, Meng; Xu, Yunfeng; Xiang, Jinle; Zheng, Bailiang; Yuan, Yuan; Luo, Denglin; Fan, Jinling
Abstract: The polyphenol profiles, antioxidant properties and inhibitory effects on α-glucosidase activities of the different milling fractions of two foxtail millet cultivars were investigated in this study. The bran of foxtail millet contained the highest free total phenolic content (TPC), while the husk had the highest bound TPC. Eighteen phenolic compounds in the free phenolic extracts and thirteen in the bound phenolic extracts from the different milling fractions of the foxtail millet were identified. For the free phenolic extracts, p-hydroxybenzaldehyde, vanillic acid and p-coumaric acid were the predominant phenolics in the husk, bran and millet, respectively. The husk of YG18 had the highest p-hydroxybenzaldehyde with the content of 101.96 mg/kg. Trans-p-coumaric acid and ferulic acid were the major phenolics in the bound phenolic extracts, and the husk of JG5 contained the highest trans-p-coumaric acid with the content of 6230.97 mg/kg. Antioxidant activities were determined by DPPH, ABTS + and FRAP assays for all the fractions, and their values are related to TPCs. The antioxidant activities of the free and bound phenolic extracts in the husk and bran were significantly higher than that in millet ( p  < 0.05). The free phenolic extracts had better inhibitory effect on α-glucosidase activity than the bound phenolic extracts, especially the free phenolics from the husk of YG18 presented the best inhibitory capacity with the lowest IC50 value of 49.88 μg ferulic acid equivalent (FAE)/mL. It was suggested that the by-products of foxtail millet could be utilized as a potential source of natural antioxidants and α-glucosidase inhibitors. Graphical abstract: Image 1 Highlights: Totally twenty-nine phenolic compounds were identified and quantified. The husk and bran contained higher contents of individual phenolic compounds. By-products of foxtail millet presented better antioxidant capacities. The free phenolics from the husk had better inhibitory effect on α-glucosidase.